Introduction to Two-Variable Equations

Hello, Year 7! Today, we’re going to learn about two-variable equations. These are equations that involve two different variables, usually represented by letters like (x) and (y).

What is a Two-Variable Equation?

A two-variable equation looks like this:

$$

y = 2x + 3

$$

In this equation, (y) depends on (x). This means whenever we choose a value for (x), we can find a corresponding value for (y).

How to Find a Value

To find a value using a two-variable equation, follow these steps:

  1. Choose a value for one variable.
  2. Substitute that value into the equation.
  3. Calculate the value of the other variable.

Example

Let’s say we have the equation:

$$

y = 2x + 1

$$

  1. Choose a value for (x): Let’s pick (x = 2).
  2. Substitute into the equation:$$y = 2(2) + 1$$
  3. Calculate (y):$$y = 4 + 1 = 5$$

So, when (x = 2), (y = 5).

Key Rules

  • Always substitute carefully.
  • Perform the calculations step-by-step.
  • You can pick any value for (x) or (y) to find the other.

Tips and Tricks

  • Start with easy numbers like 0 or 1 to practice.
  • Check your work by substituting back into the original equation.
  • Remember that one equation can have many pairs of (x) and (y).

Practice Questions

Easy Level Questions

  1. If (y = 3x + 2), find (y) when (x = 1).
  2. If (y = 2x – 4), find (y) when (x = 0).
  3. If (y = x + 5), find (y) when (x = 3).
  4. If (y = 4x), find (y) when (x = 2).
  5. If (y = x – 1), find (y) when (x = 5).
  6. If (y = 2x + 3), find (y) when (x = 4).
  7. If (y = 5x), find (y) when (x = 1).
  8. If (y = x + 2), find (y) when (x = 0).
  9. If (y = 6x – 1), find (y) when (x = 2).
  10. If (y = 7 – x), find (y) when (x = 3).
  11. If (y = 3x + 1), find (y) when (x = 2).
  12. If (y = 4 – x), find (y) when (x = 2).
  13. If (y = 2x), find (y) when (x = 5).
  14. If (y = x + 3), find (y) when (x = 1).
  15. If (y = 10 – 2x), find (y) when (x = 4).
  16. If (y = 8x + 1), find (y) when (x = 0).
  17. If (y = x + 4), find (y) when (x = 2).
  18. If (y = 5 – x), find (y) when (x = 1).
  19. If (y = 3x – 5), find (y) when (x = 3).
  20. If (y = 2x + 2), find (y) when (x = 1).

Medium Level Questions

  1. If (y = 2x + 5), find (y) when (x = 3).
  2. If (y = 3x – 2), find (y) when (x = 4).
  3. If (y = 4 – 3x), find (y) when (x = 1).
  4. If (y = 5 + 2x), find (y) when (x = 2).
  5. If (y = 7x + 1), find (y) when (x = 0).
  6. If (y = 6 – 2x), find (y) when (x = 3).
  7. If (y = 4x + 4), find (y) when (x = 5).
  8. If (y = 3 – x), find (y) when (x = 2).
  9. If (y = 8x – 3), find (y) when (x = 1).
  10. If (y = x^2 + 2), find (y) when (x = 2).
  11. If (y = 2x^2 – 4), find (y) when (x = 2).
  12. If (y = 5 – x^2), find (y) when (x = 1).
  13. If (y = 10 + 3x), find (y) when (x = 0).
  14. If (y = 2 – 4x), find (y) when (x = 1).
  15. If (y = 1 + 5x), find (y) when (x = 3).
  16. If (y = x/2 + 5), find (y) when (x = 6).
  17. If (y = 9 – 2x), find (y) when (x = 4).
  18. If (y = 4 + 3x), find (y) when (x = 0).
  19. If (y = 7 – x^2), find (y) when (x = 3).
  20. If (y = 2x + 6), find (y) when (x = 5).

Hard Level Questions

  1. If (y = 3x^2 – 2x + 1), find (y) when (x = 2).
  2. If (y = 5 – x^2 + 3x), find (y) when (x = 1).
  3. If (y = 4x^2 – 3x + 2), find (y) when (x = 3).
  4. If (y = x^2 + 5x – 6), find (y) when (x = -1).
  5. If (y = 2x^2 + x + 4), find (y) when (x = 2).
  6. If (y = 3x^2 – 4x + 1), find (y) when (x = 1).
  7. If (y = 5x – x^2 + 4), find (y) when (x = 3).
  8. If (y = 6 – x^2 + 2x), find (y) when (x = 2).
  9. If (y = 2x + 3x^2 – 1), find (y) when (x = 1).
  10. If (y = 4x^2 + 3x – 2), find (y) when (x = -1).
  11. If (y = 7 – 2x^2 + 5x), find (y) when (x = 1).
  12. If (y = -x^2 + 6x – 5), find (y) when (x = 2).
  13. If (y = 3x^2 – 5x + 2), find (y) when (x = 3).
  14. If (y = 2 + 3x – 4x^2), find (y) when (x = 1).
  15. If (y = x^2 – 2x + 5), find (y) when (x = 3).
  16. If (y = 5x + x^2 – 3), find (y) when (x = 2).
  17. If (y = 4x – 3x^2), find (y) when (x = 1).
  18. If (y = 2x^2 + 3 – x), find (y) when (x = 4).
  19. If (y = -x^2 + 4x + 1), find (y) when (x = 5).
  20. If (y = x^2 – 1 + 3x), find (y) when (x = -2).

Answers and Explanations

Easy Level Answers

  1. (y = 3(1) + 2 = 3 + 2 = 5)
  2. (y = 2(0) – 4 = 0 – 4 = -4)
  3. (y = 3 + 5 = 8)
  4. (y = 4(2) = 8)
  5. (y = 5 – 1 = 4)
  6. (y = 2(4) + 3 = 8 + 3 = 11)
  7. (y = 5(1) = 5)
  8. (y = 0 + 2 = 2)
  9. (y = 6(2) – 1 = 12 – 1 = 11)
  10. (y = 7 – 3 = 4)
  11. (y = 3(2) + 1 = 6 + 1 = 7)
  12. (y = 4 – 2 = 2)
  13. (y = 2(5) = 10)
  14. (y = 1 + 3 = 4)
  15. (y = 10 – 8 = 2)
  16. (y = 8 + 1 = 9)
  17. (y = 5 – 1 = 4)
  18. (y = 2 + 3x = 2 + 12 = 14)
  19. (y = -9 + 20 + 1 = 12)
  20. (y = 2 + 3 = 5)

Medium Level Answers

  1. (y = 2(3) + 5 = 6 + 5 = 11)
  2. (y = 3(4) – 2 = 12 – 2 = 10)
  3. (y = 4 – 3(1) = 4 – 3 = 1)
  4. (y = 5 + 2(2) = 5 + 4 = 9)
  5. (y = 0 + 1 = 1)
  6. (y = 6 – 2(3) = 6 – 6 = 0)
  7. (y = 4(5) + 4 = 20 + 4 = 24)
  8. (y = 3 – 2 = 1)
  9. (y = 8(1) – 3 = 8 – 3 = 5)
  10. (y = 4 + 8 – 6 = 6)
  11. (y = 2(2)^2 – 4 = 8 – 4 = 4)
  12. (y = 5 – 1 = 4)
  13. (y = 10 + 0 = 10)
  14. (y = 1 – 4 = -3)
  15. (y = 1 + 15 = 16)
  16. (y = 3 – 12 + 2 = -7)
  17. (y = 4 + 0 = 4)
  18. (y = 4 + 3 = 7)
  19. (y = 7 – 9 = -2)
  20. (y = 10 + 12 = 22)

Hard Level Answers

  1. (y = 3(2)^2 – 2(2) + 1 = 12 – 4 + 1 = 9)
  2. (y = 5 – 1 + 3 = 7)
  3. (y = 4(3)^2 – 3(3) + 2 = 36 – 9 + 2 = 29)
  4. (y = 1 + 5 – 6 = 0)
  5. (y = 2(2)^2 + 2 + 4 = 8 + 2 + 4 = 14)
  6. (y = 3(1)^2 – 4(1) + 1 = 3 – 4 + 1 = 0)
  7. (y = 5(3) – (3^2) + 4 = 15 – 9 + 4 = 10)
  8. (y = 6 – 4 + 4 = 6)
  9. (y = 2(1) + 3(1)^2 – 1 = 2 + 3 – 1 = 4)
  10. (y = 4(-1)^2 + 3(-1) – 2 = 4 – 3 – 2 = -1)
  11. (y = 7 – 2(-1)^2 + 5(-1) = 7 – 2 – 5 = 0)
  12. (y = -(-2)^2 + 6(-2) – 5 = -4 – 12 – 5 = -21)
  13. (y = 3(3)^2 – 5(3) + 2 = 27 – 15 + 2 = 14)
  14. (y = 2 + 3(1) – 4(1)^2 = 2 + 3 – 4 = 1)
  15. (y = 9 – 6 + 5 = 8)
  16. (y = 4(1) – 3(1^2) = 4 – 3 = 1)
  17. (y = 2(4^2) + 3 – 4 = 32 + 3 – 4 = 31)
  18. (y = -2^2 + 4(-2) + 1 = -4 – 8 + 1 = -11)
  19. (y = -5^2 + 20 – 3 = -25 + 20 – 3 = -8)
  20. (y = (-2)^2 – 1 + 3(-2) = 4 – 1 – 6 = -3)

I hope this helps you understand how to find values using two-variable equations! Keep practicing, and you’ll get even better!